Ultrasound-Guided Corticosteroid Injection in Carpal Tunnel Syndrome: Comparison Between Radial and Ulnar Approaches - Babaei-Ghazani, Arash (J Pain Res, 2020)
PURPOSE: To compare two common approaches for ultrasonography (US)-guided injection. PATIENTS AND METHODS: Sixty patients with mild-to-moderate CTS were included in this double-blind randomized controlled trial (RCT). They received a single shot of corticosteroid injection through either the US-guided in-plane approach: radial or ulnar side. Participants were evaluated using Boston Carpal Tunnel Questionnaire (BCTQ) and visual analogue scale (VAS) for pain, as well as electrodiagnosis (EDX) and US parameters before the intervention, and within 12 weeks of follow-up. RESULTS: In both groups, all outcomes, except for the electrodiagnostic measures, significantly improved within the follow-up. Pain-VAS and both subscales of BCTQ questionnaire, as our main subjective outcomes, revealed dramatic improvement, with the largest amount of changes in VAS (70%; comparing to baseline value), and about 37% for both of BQSS and BQFS scales, all indicating superiority of radial to ulnar in-plane approach. During the first follow-up, we did not detect any remarkable preference between the groups in either subjective or electrodiagnostic variables. However, there was a significant difference at next follow-up time-points in terms of VAS for pain and BQFS favoring radial approach (Table 3). Furthermore, US-measured parameters including nerve-circumference and CSA improved only in the radial in-plane group. CONCLUSION: The current data proved that radial in-plane approach for CTS injection could be at least as effective as the more common ulnar in-plane method. Even the pain-relief effect was longer for the radial in-plane approach. Also, patients’ functional status and objective variables all revealed better outcomes via the new approach.